Clock gene Bmal1 controls diurnal rhythms in expression and activity of intestinal carboxylesterase 1. (19th February 2021) - Chen, Xun; Yu, Fangjun; Guo, Xiaolei; Su, Chong; Li, Shu-Shu; Wu, Baojian
Abstract: Objectives: We aimed to characterize diurnal rhythms in CES1 expression and activity in mouse intestine, and to investigate a potential role of the core clock gene Bmal1 in generating diurnal rhythms. Methods: The regulatory effects of intestinal Bmal1 on diurnal CES1 expression were assessed using intestine-specific Bmal1 knockout ( Bmal1 iKO ) mice and colon cancer cells. The relative mRNA and protein levels were determined by qPCR and Western blotting, respectively. Metabolic activity of CES1 in vitro and in vivo were determined by microsomal assays and pharmacokinetic studies, respectively. Transcriptional gene regulation was investigated using luciferase reporter assay. Key findings: Total CES1 protein varied significantly according to time of the day in wild-type ( Bmal1 fl/fl ) mice, peaking at ZT6. Of detectable Ces1 genes, Ces1d mRNA displayed a robust diurnal rhythm with a peak level at ZT6, whereas mRNAs of Ces1e, 1f and 1g showed no rhythms in wild-type mice. Loss of intestinal Bmal1 reduced the levels of total CES1 protein and Ces1d mRNA, and blunted their diurnal rhythms in mice. In vitro microsomal assays indicated that intestinal metabolism of mycophenolate mofetil (MMF, a known CES1 substrate) was more extensive at ZT6 than at ZT18. ZT6 dosing of MMF to wild-type mice generated a higher systemic exposure of mycophenolic acid (the active metabolite of MMF) as compared with ZT18 dosing. Intestinal ablation of Bmal1 down-regulated CES1 metabolism at ZT6, and abolished its time-dependency both in vitro and in vivo . Furthermore, Ces1d/CES1 rhythmicity and positive regulation of Ces1d/CES1 by BMAL1 were confirmed in CT26 and Caco-2 cells. Mechanistically, BMAL1 trans-activated Ces1d/CES1 probably via binding to the E-box elements in the gene promoters. Conclusions: Bmal1 controls diurnal rhythms in expression and activity of intestinal CES1. Our findings have implications for understanding the crosstalk between circadian clock and xenobiotic metabolism in the intestine.